Den hierarkiske anarkisme: Indflydelsen af politiske overbevisninger på Volksbühnes infrastruktur - Otterstrøm, Sara (Peripeti, 2018)
How did the Volksbühne Theatre arise and which values does it embrace? To which degree has the artistic content and the organisational structure been influenced by politics? By using examples and witness reports, a picture of Volksbühne’s identity in the political landscape is drawn.